Trade and competitiveness: Putting the firm at the centre of the analysis - Lucian Cernat; Oscar Guinea (European Centre for International Political Economy (ECIPE), 2023)
The European Commission published its communication for the long-term competitiveness of the EU. Trade and Open Strategic Autonomy were among the selected policy areas that will drive EU competitiveness in the future and trade with the rest of the world as a share of EU Gross Domestic Product (GDP) was the selected indicator to measure progress. This Policy Brief proposes a new set of indicators that complement this and similar indicators that focus on the value of trade. Using the Trade by Enterprise Characteristics (TEC) database, this paper produces indicators that measure the number of exporters, non-EU suppliers, non-EU customers, and foreign companies. By putting the firm at the centre of the analysis, these indicators offer insights that complement policy-makers' views on trade and competitiveness.
Keywords: 330